Analysis of Peer Editing Technique to Foster Students' Collaboration Character in Pancasila Education Learning - Zahrah, Hanani Akiluz; Murdiono, Mukhamad (International Journal of Social Service and Research, 2025)
Civic Education aims to shape national life through values and character education. Character is an essential trait that defines individuals and distinguishes them from others. This study aims to analyze peer editing techniques in shaping the character of student cooperation in learning Pancasila Education. The peer editing technique involves students acting as peers in providing feedback on infographic tasks carried out in groups. This technique, through its process, teaches students a sense of group unity, develops values of care, and encourages sharing among fellow students—forming a foundation for cooperation in learning. Additionally, students tend to feel more free and comfortable when engaging in activities with their peers, which in turn helps to foster a cooperative character. This research uses a qualitative descriptive methodology and seeks to build an understanding (verstehen) and explanation of human behavior as social beings. It also aims to construct knowledge based on a constructive perspective, derived from the author's experiences and prevailing social values.